Agriculture and Agricultural Cooperatives in Japan - A Model for Cooperativization of Agriculture from Romania - Remus Gherman; Ana-Mariana Dincu; Anda Milin; Ioan Brad (Scientific Papers Animal Science and Biotechnologies, 2023)
Japan's agriculture provides only a part from the population's needs, in caloric terms Japan must impute 60% of foods. Arable land are few, but are worked very performant, rice being the main crop together with cotton, citrus, sugarcane, wheat, potato, soybean, sugar beet, other vegetables. Widely is practiced sericulture and fisheries, Japan being one of the leading producers of silk from the world and having over 600 ports specialized for fishing. Japanese agriculture has remained behind the industry and services, this trend being manifested after the very high economic growth from 1960-1970. The main focus of the movements from the Japanese cooperative system is represented by the creation of large specialized farms through the replacing of the traditional ones. The most important task of agricultural cooperatives from Japan is meeting the consumption needs of its members. Integrated leadership of Japanese cooperatives of farmers act at all levels, primary, at prefecture level and at national level. Contractual relationships play a decisive role in the integration of Japanese farmers. In Japan there are about 840 agricultural cooperatives very well organized with a balanced planning and efficiently conducted, agricultural cooperative MIKABI being the most developed, mainly focused on the production of mandarins. In Japan there are three large distribution centers of agricultural products, 29 distribution markets controlled by the prefecture and 1,000 local markets. Organization of cooperatives is the pyramid system on three levels: local, prefecture and national (National Federation of Agricultural Cooperatives).